MXene-based electrolyte for vanadium-bromide redox flow battery for green energy - Hossain, Md.Hasnat; Abdullah, Norulsamani; Rahman, S.; Mohd Radzi, Mohd Amran (Elsevier, 2023)
New promising technology has been developed in 1984 for vanadium redox flow batteries into stagnant energy storage. Compared to other redox flow battery systems, this technology is very efficient, low cost, and has longer life. However, vanadium redox flow batteries need to overcome low thermal conductivity, low diffusivity, high resistivity, high liquid density, and low energy efficiency. This study aims to use MXene in vanadium (IV) electrolytes to improve thermal conductivity and diffusivity and reduce resistivity. The vanadium (IV) electrolyte-based nanofluid was studied with a different weight percentage of MXene (0.5 wt, 1 wt, 1.5 wt, and 2.0 wt). Several physical, thermal and electrochemical characterizations like FTIR, UV–vis, SEM, EDX, and thermal properties measurements were performed. The FTIR, UV–vis and SEM, and EDX show there is no additional peak observed, the reduced light transmission capability was enhanced and smooth 2D layered structures of MXene were obtained. MXene-based electrolyte’s highest value of thermal conductivity was increased against base solution by 29.8 , 53.6 , 70.3 , and 75.9 , and the resistivity decreased by 30.7 , 47.4 , 65.2 , and 68.9 , respectively. The best thermal conductivity increased by 75.9 using 2 wt MXene at 45 C. Due to the enhancement of physical, thermal, and electrochemical characterizations, this study will help guide future research to improve green energy storage technology and reach some of the sustainable development goals (SDG) to ensure the access to affordable, reliable, sustainable and green modern energy for all.